The Effect of Current Ratio, Return on Assets, and Total Assets Turnover on Firm Value with Company Size as a Moderating Variable in The Manufacturing Sector - Indah, Chintiya Manisha; Suryadi, Edy (UNIVERSITAS PAKUAN, 2025)
This study aims to examine the effect of Current Ratio, Return on Assets, and Total Assets Turnover on firm value with Firm Size as a moderating variable in the manufacturing sector listed on the Indonesia Stock Exchange (IDX) during the period 2021-2023. The use of financial ratios such as Current Ratio, Return on Assets, and Total Assets Turnover is expected to provide insights into the financial health of companies related to increases in company value. This study employs an associative quantitative approach using secondary data obtained from annual reports of companies meeting specific criteria. The sample consists of 43 manufacturing companies listed on the IDX. Data analysis was conducted using Moderated Regression Analysis (MRA) and classical assumption tests, including normality, multicollinearity, autocorrelation, heteroskedasticity, and linearity tests. The results indicate that Current Ratio and Return on Assets significantly influence company value, while Total Assets Turnover does not show a significant influence. Company size was found to moderate the influence of Return on Assets on firm value, but did not moderate the influence of Current Ratio and Total Assets Turnover. The resulting regression model explained 86.5% of the variation in firm value. This study provides important insights for investors and company management to consider financial ratios, particularly Return on Assets, in assessing investment potential and strategies for enhancing firm value.